Financial Ratio and Its Influence to Profitability in Islamic Banks. - Erika Amelia (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
This research aims to analyze the influence of the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Biaya Operasional Pendapatan Operasional (BOPO) to Return on Asset (ROA) in Bank Muamalat Indonesia and Bank Syariah Mega. The data analysis method used in this research is multiple regression analysis. From the test results show that the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR) and Biaya Operasional Pendapatan Operasional (BOPO) simultaneously effect to Return on Asset (ROA). Based on the test results of the t statistic was concluded that the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF) and the Financing to Deposit Ratio (FDR) partially no significant effect to Return on Asset (ROA), while Biaya Operasional Pendapatan Operasional (BOPO) partially significant effect to Return on Asset (ROA)DOI: 10.15408/aiq.v7i2.1700